Compressive and shear behavior of brick masonry assemblages strengthened with polyurea coating: Experiment and DEM investigations. (19th September 2022) - Cuong, Nguyen Huu; Shin, Jiuk; Kim, Jae Hyun; Luat, Nguyen-Vu; Lee, Kihak
Abstract: Over the last few years, a huge amount of effort has been spent on developing numerical models to improve knowledge of methods to strengthen concrete and brick structures under various conditions. This paper evaluated the ability of the Discrete Element Method (DEM) to accurately predict the mechanical behavior of brick masonry. Two different specimens were tested for compression and direct shear, with and without polyurea reinforcement of the brick masonry. Detailed numerical models of the brick masonry were generated using the commercial software Three-Dimensional Distinct Element Code (3DEC) to compare the laboratory test results against simulation for both cases. The numerical and experimental results were found to be in good agreement, which demonstrates the efficiency and stability of the DEM for simulating brick masonry behavior. Another purpose of this research was to evaluated the effect of parameters on the numerical model, including mesh size, material cohesion, friction, and dilation. These important findings can be used to calibrate material model parameters for strengthening brick masonry in the future. Highlights: The experiment of brick masonry assemblages with/without polyurea coating. Both compression and direct shear tests were carried out. Commercial software 3DEC was utilized to verify the experiment results. Parametric studies for strengthening brick masonry assemblages were investigated.